PROMOTIONAL STRATEGY TO INCREASE COMPUTER SALES USINGSUPPLY CHAIN : (CASE STUDY: GLOBAL TEKNIK) - Dominggus Umbu Dedo; Trisno; Martinus Malo Ngongo (CV. Fahr Publishing, 2023)
In the current era of globalization, the world of information is developing very rapidly because it is supported by increasingly sophisticated technological developments. Computers are a tool to support the development of information technology. Therefore, an institution that uses computers to manage its information system will have more value than a system that is processed manually. Current technological developments are very diverse in various aspects of life so that they really help human activities every day. This includes the development of computer technology with various applications used in various scientific disciplines. It is hoped that this technology, which was born thanks to human creativity and innovation, can regenerate new creativity and innovation in various fields, marking the progress of this technology. One area that cannot be separated from the use of technology is education. Based on the analysis carried out, Global Teknik increases sales volume with product diversification strategies, building rapport with suppliers, setting affordable prices, continuous promotions through advertising in various media that can attract consumer purchasing interest. It can be concluded that the right marketing strategy in global engineering can increase sales volume.